Greenhouse and field assessment of different organic compounds against guava-parasitic Meloidogyne enterolobii - Alexandre Macedo Almeida (Bragantia, 2012)
Guava decline is a complex disease involving Meloidogyne enterolobii and Fusarium solani and it has caused major direct losses to Brazilian growers. Although several strategies have been sought to control the nematode, the use of organic soil amendments is currently the best approach to manage this disease. To assess the best amount of meat and bone meal (MBM) to be incorporated into the soil, guava seedlings inoculated with M. enterolobii were treated with 1-5% v/v of the MBM. Ninety days later variables related to nematode reproduction and plant development were evaluated, which indicated a potential nematicidal effect of the MBM at 3%. Another experiment assessed nematode- and plant-related variables 90 days after treatment of the seedlings with MBM, chitosan, shrimp shell or neem cake at 3%, 0.05%, 2% and 0.1% v/v, respectively. The MBM ranked first, reducing nematode reproduction. This MBM rate was converted to 25 kg/tree and assessed in three application regimes (monthly, bimonthly or trimonthly), for six months, in an orchard affected by guava decline. The variables assessed were soil density of colony forming units (CFU) of bacteria and fungus, and soil and/or root density of M. enterolobii, Helicotylenchus sp., and of different nematode trophic groups. In all three application regimes the MBM reduced all plant-parasitic nematodes in the soil and the fungus CFUs. It also promoted an increase in bacterial CFU and bacterivorous nematodes.